Auditory performance of cochlear implant children aged 2-5 years - Cheamchit Thawin (2018)
Objective: To assess the categories of auditory performance in prelingual deaf children after implantation. Study design: Prospective study Material and Method: The present study consisted of one boy and four girls aged between 2 and 5 years old at the time of implantation. All subjects had bilateral profound sensorineural hearing loss and received no substantial benefit from amplification. Three subjects were implanted with Med-El combi 40+ with CIS strategy and two subjects received multichanal monopolar Nucleus 24 cochlear implant with ACE strategy. After implantation, all subjects undertook a program of habilitation at the Speech and Hearing Clinic Ramathibodi Hospital. The Categories of Auditory Performance (CAP) score was determined at regular intervals prior to implantation, immediately at the initial mapping (0) and 3, 6,12 and 18 months after the implantation. Results: The results showed that before implantation, only three children showed awareness of environment sounds, CAP score level 1, and that immediately after mapping, all of the children demonstrated awareness of the environmental sounds. Moreover, two of these children showed awareness of speech sounds, CAP score level 2. The CAP scores were gradually increased over a 12-month period. At the 12-month assessment interval, four children could discriminate two speech sounds, CAP score level 4 and one child understood phrases without lip reading, CAP score level 5. 18 months after of implantation, the CAP score for four children increased to level 5. One child understood conversation without lip reading with a familiar talker, CAP score level 6. Furthermore, children with congenital hearing loss who underwent implantation at a younger age received more benefit from the implantation. Conclusion: The CAP score was found to be a useful and sensitive tool to evaluate the outcome of auditory receptive abilities in young congenital deaf children who underwent cochlear implantation. The accessible outcome measurement will provide information for parents and professionals to obtain a hierarchical scale on which the children's auditory ability with other more formal measures may be inappropriate.